ANALISIS KEMAMPUAN PROBLEM SOLVING DAN IDENTIFIKASI MISKONSEPSI SISWA MELALUI TES DIAGNOSTIK MULTI-TIER BERBASIS GOOGLE FORMS PADA MATERI FISIKA - Dorlita Sidabutar; Icha Nia Nirwani Pasaribu; Santi Sihombing; Tsuraya Nur Kholila; Mariati Purnama Simanjuntak (STKIP Subang, 2026)
This study aims to analyze the needs for developing and implementing a Google Forms-based multi-tier diagnostic test in physics learning at three senior high schools in Medan: SMA Negeri 18 Medan, SMA Negeri 13 Medan, and SMA Swasta PAB 8 Saintis. A qualitative descriptive approach with a survey method was employed. Data were collected through interviews and questionnaires involving 54 respondents, consisting of 51 students from grades X and XI of the science program and 3 physics teachers. The results indicate that 70% of students find physics difficult and 65% tend to memorize formulas rather than understand concepts. About 57% of students identified lack of basic conceptual understanding as the primary cause of misconceptions. Students' critical thinking and problem-solving abilities remain low, with 55% struggling in critical thinking and 60% in problem solving. Nevertheless, 85% of students responded positively to Google Forms usage, and 82% reported that the multi-tier diagnostic test helped improve their conceptual understanding and problem-solving skills.